1987
DOI: 10.1111/j.1398-9995.1987.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to penicillin in children receiving long‐term secondary prophylaxis for rheumatic fever

Abstract: The occurrence of IgE and IgG antibodies to penicillin G and V in children on long-term treatment with penicillin as secondary prophylaxis for rheumatic fever was studied using Phadebas RAST (Pharmacia Diagnostics, Uppsala, Sweden) and ELISA respectively. The duration of the prophylaxis ranged between 1.5 months and 5 years (mean 1.8 years). Of 18 patients who had been given penicillin for more than 1.5 months, two had IgE antibodies and 12 had IgG antibodies to penicillin. Patients with acute rheumatic fever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It has also been suggested that they may be able to prevent anaphylactic shock in penicillin‐allergic subjects by their blocking ability ( 3). IgG antibodies to penicillin have been studied by different authors using different methods and with variable results ( 24–26). Levine et al observed that 100% of subjects receiving penicillins developed IgG antibodies ( 14).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that they may be able to prevent anaphylactic shock in penicillin‐allergic subjects by their blocking ability ( 3). IgG antibodies to penicillin have been studied by different authors using different methods and with variable results ( 24–26). Levine et al observed that 100% of subjects receiving penicillins developed IgG antibodies ( 14).…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients do not have a clinically evident IDR when treated with a drug, there may be an immune response. For example, most patients who are treated with penicillin develop antipenicillin antibodies but in most cases they are IgG antibodies and there is no adverse reaction (Strannegård et al, 1987). Furthermore, almost all patients treated with procainamide for an extended period of time develop autoantibodies, but most do not develop a clinical autoimmune syndrome (Woosley et al, 1978).…”
Section: Immune Response Assaysmentioning
confidence: 99%
“…Nevertheless, a considerable overlap exists between immediate and accelerated reactions and the latter are very often classified as immediate reactions, contributing to their misclassification. Mechanisms involving an IgE mediated response have been proposed for serum sickness and delayed urticaria, though current knowledge is insufficient to confirm this [18][19][20][21]. However, a detailed analysis of this is beyond the scope of this review, although it is nevertheless an interesting hypothesis.…”
Section: Introductionmentioning
confidence: 94%